Correction of procedure for conversion of gas-dynamic characteristics of high-pressure centrifugal сompressor stage in case of frequency change rotor rotation - A. D. Vanyashov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The proposed corrected method of conversion of gas-dynamic characteristics of high-pressure stage of turbocharger operating in the area of high circumferential speeds (conditional Mach numbers > 0,5) to other rotor speeds is given in the work, taking into account deviation from kinematic and dynamic similarity conditions. The method of combined control due to creation of swirling of flow in front of impeller and simultaneous change of rotation speed is considered. Analysis of experimental and theoretical results is done.